Where Should We Intervene, 20 Years Later? Case–Control and Prospective Cohort Designs Provide Similar Answers - Blais, Julie (Criminal justice and behavior, 2025)
In 2000, this journal published an influential case–control study identifying dynamic risk factors for sexual recidivism (Hanson & Harris, 2000). In 2017, updated recidivism information for the same sample was obtained with an average follow-up of 20 years. The current study compared the risk factors that differentiated between sexual recidivists and nonrecidivists between the two research designs: original case–control and updated prospective cohort. Of the 82 comparisons, 50 favored the prospective design while 32 favored the case–control; however, most of the differences were small and nonsignificant. Static and dynamic risk factors were approximately equivalent between study designs. Factors identified as sex-specific (e.g., sexual deviancy) were also equivalent between designs while general risk factors (e.g., substance use) were more likely identified in the prospective design. Overall, case–control studies can be used for the identification of risk factors, especially for low base rate behaviors such as sexual recidivism.